Community Survey on Blood Pressure and Levels of Blood Glucose, Cholesterol and Uric Acid Among People 45 Years and Above in Rural Villages of Bali - Putu Sutisna (Scopus ID: 6506044199); I Ketut Tangking Widarsa; I Wayan Darwata; I Nengah Kapti (Warmadewa University, 2022)
OBJECTIVE. To observe the proportion of high blood pressure and high blood glucose, cholesterol and uric acid among people aged 45 years and older at the rural villages of Pejeng, Samplangan and Petak, in Gianyar Regency, Bali. METHODS. The surveyâ€™s samples were all persons aged 45 years and over who came voluntarily to participate in the survey. Blood pressure was measured by mercury sphygmomanometer (Nova). Non-fasting levels of serum glucose, cholesterol, and uric acid were assessed by rapid test method using Easy Touch CGU apparatus. Each parameter studied was categorized as â€œhighâ€ and â€œnormalâ€ (blood pressure high: â‰¥140/90 mmHg; blood cholesterol high: â‰¥200mg/dl; blood glucose high â‰¥200mg/dl; blood uric acid high: >7.0 mg/dl, while other measurements below those values were categorized as normal. Data were analyzed descriptively and presented in tables of frequencies. RESULTS. A total of 650 people aged 45 years and above participated in the survey (Samplangan village: 157 people, Pejeng village: 168 people, Petak village: 225 people). Of 650 study subjects examined, 43.8% had high serum cholesterol, 22.8% had high blood pressure, 26.3% had high serum uric acid, and 9.8% had high blood glucose. According to gender, 49.5% males and 38.2% females had high blood cholesterol, 27.3% males and 20.5% females had high blood pressure, 38.4% males and 20.3% females had high blood uric acid, and 11.1% males and 9.4% females had high blood glucose, respectively CONCLUSIONS. In respective three villages greatest proportion of the study subjects had high serum cholesterol, followed in order of decreasing proportions by either high blood pressure or high blood uric acid, and the lowest proportion was with high blood glucose.